My Father, Between Poetry and Family - Aguilar Rodríguez, Silvia (2024)
Silvia Aguilar, his youngest daughter, gives an insight into the intimacy of the poet Marco Aguilar’s family life. With this, it is possible to learn not only about his strong emotional bonds with his parents, wife, ex-wife, siblings and children, but also about aspects that allow us to better understand the character and hobbies of Marco, as well as some of the factors that shaped his personality, which undoubtedly influenced his written work.